2006
DOI: 10.1002/pen.20419
|View full text |Cite
|
Sign up to set email alerts
|

Nonisothermal comprehensive 3D analysis of polymer melt flow in a coat‐hanger die

Abstract: The nonisothermal flow of Carreau fluid in a coat-hanger die is studied. A general three-dimensional finite volume code is developed for the purpose of flow analysis. The isobars, the isotherms, and the velocity distribution are obtained. Simulation results illustrated that the highest temperature occurred by the center of manifold, rather than the die-lip region because of the combined effects of high shear rate and poor heat conduction, which is important for processing those heat-sensitive materials. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Velocity is calculated based on the method given by Kim [17].Velocity and temperature profiles are adapted from Wei and Michaeli [5,18,19]. In this method, velocity is given as follows: (9) where:…”
Section: Inflow Boundary Conditionmentioning
confidence: 99%
See 1 more Smart Citation
“…Velocity is calculated based on the method given by Kim [17].Velocity and temperature profiles are adapted from Wei and Michaeli [5,18,19]. In this method, velocity is given as follows: (9) where:…”
Section: Inflow Boundary Conditionmentioning
confidence: 99%
“…Huang et al [8] analyzed flow distribution of polymer melt in the coat-hanger extrusion die for the purpose of understanding flow behavior, such as dead spots in the die cavity. Wu et al [9] also studied the flow and temperature fields of the coat-hanger die. They concluded that the highest temperature, which is important for temperature-sensitive polymers, occurs at the center of the manifold.…”
Section: Introductionmentioning
confidence: 99%
“…At the border area of the manifold and the slot, the denser meshes are used because of the abrupt change in the geometry. In the simulation the nonslip boundary condition14–16 is applied on the die wall for the three velocity components. At the symmetry plane, zero x‐component velocity and zero surface traction in y and z directions are imposed.…”
Section: Introductionmentioning
confidence: 99%
“…The derived equation was based on an average momentum and mass balance within the cavity. Wu et al10 studied the nonisothermal flow of Carreau fluid in the coat‐hanger die. The isobars, the isotherms, and the velocity distribution were obtained as well.…”
Section: Introductionmentioning
confidence: 99%